Analytical Methods in Plasma Diagnostic by Optical Emission Spectroscopy : A Tutorial Review - Ley, Hood-Hong (Journal of Science and Technology, 2014)
This article reviews on the basic data processing technique and plasma diagnosis method by optical emission spectroscopy. The review is focused on the physical concepts of an analysis methods and its application to determine the plasma parameters. Processing procedures such as signal averaging and spectrum smoothing technique such as boxcar are discussed. Next, conditions such as local thermodynamic equilibrium plasma were briefly discussed with the method available to assess its existence. Similarly, the available techniques to quantitatively determine optically thin condition of spectral line are considered including method to calculate the suitable time window for a spectral line to be optically thin. Measurement techniques of plasma temperature and electron density were compared and contrast to gauge the advantages of each technique.